Pembuatan Laporan Keuangan pada Proyek Pembangunan Asrama dan Kelas Yayasan Madinah Al-Hijrah Pandeglang Banten - Mahroji (DPPM Universitas Pelita Bangsa, 2026)
The construction of dormitories and classrooms at Yayasan Madinah Al-Hijrah, Pandeglang, Banten, is a strategic step to enhance the quality of education and facilities for students. This project aims to provide a better learning environment and support character development among students. The methods used in the preparation of financial reports include data collection, cost analysis, and evaluation of fund utilization. The results of this project indicate that transparent and accountable financial management is crucial for ensuring the success of the construction. In conclusion, a well-prepared financial report can serve as an important tool for project planning and oversight, as well as increase community trust in the foundation.